ANALISIS TINGKAT KEJENUHAN MAHASISWA PROGRAM STUDI TEKNIK INFORMATIKA PADA MATA KULIAH BAHASA INDONESIA - Nia Damayanti (Jurnal Ilmu Pendidikan dan Sosial, 2022)
The purpose of this research is to know the level of boredom of student learning in Indonesian subjects at the Informatics Engineering Study Program, Indraprasta University, PGRI Jakarta during the pandemic. This study uses a descriptive qualitative technique where the sample used in this study amounted to 40 students from the regular morning class of RH and RI each 20 students using purposive sampling technique. The data from this study were taken using a student learning saturation questionnaire with a total of 40 questions. And refers to the saturation level indicator which is then processed with statistical descriptions. The results of the study showed that student learning saturation was known to 7 people (17.5%) had a low level of saturation, 15 people (37.5%) had a moderate level of saturation, while those who had a high saturation category were 18 people (45%). From the results of the calculation of the average value obtained a value of 36.8, it is included in the low category, so it can be concluded that the level of saturation of the students of the informatics engineering study program in the Indonesian language course is low.